Role of clinical oncology pharmacist in determination of pharmaceutical care needs in patients with colorectal cancer - SANCAR, MESUT; YUMUK, PERRAN FULDEN; TEZCAN, SONGÜL (BMJ PUBLISHING GROUP, 2018)
Objective To determine and evaluate the pharmaceutical care needs and quality of life of patients with colorectal cancer. Methods 36 Patients with colorectal cancer eligible for chemotherapy after surgery were included in the study. The patients were followed up during 3 courses of chemotherapy and individual pharmaceutical care plans were developed. The quality of life of patients was evaluated before and after the third course of chemotherapy. Results The incidence of drug-related problems (DRPs) in chemotherapy-treated patients was reduced in the 3rd course as compared with 1st course (63.9% vs 75%, respectively; n = 36; p > 0.05). The clinical oncology pharmacist gave 147 recommendations to patients, which were followed in 98% (n = 144) of cases. 91.7% (n = 132) of the recommendations of clinical oncology pharmacists solved the drug-related problems; however, the remaining 8.3% (n = 12) did not solve the problems and the patients were referred to a doctor for further investigations. The symptom-related quality of life of patients related to anaemia, diarrhoea and neurotoxicity was reduced after the third course of chemotherapy (p < 0.05). Conclusions The pharmaceutical care provided by the clinical oncology pharmacist has an important role in the identification and resolution of DRPs. Evaluation of symptom-related quality of life is important for the monitoring of patients receiving chemotherapy.
Keywords: Colorectal cancer; clinical oncology pharmacist; pharmaceutical care; quality of life; drug related problems; QUALITY-OF-LIFE; CHEMOTHERAPY; NEUROTOXICITY; OUTCOMES; ANEMIA